Medical Technology in Use: A History of Clinical Thermometry in Modern Britain and Japan. Issue 1 (1st March 2019) - Takabayashi, Akinobu
Abstract: Modern medicine has developed a number of technologies to observe, diagnose, and intervene in the human body. Medical technologies make bodies visible by number and form. Many historians have studied how such medical technologies as the stethoscope, pulse meter, cardiograph, and thermometer were invented and subsequently influenced societies. However, recent historians have turned their attention to the technology-in-practice to show a unidirectional history intertwined by devices, clinicians, and users. This paper aims to follow this line of study by focusing on a history of clinical thermometry in modern Britain and Japan. First, it surveys secondary works on medical technologies in history and explores how clinical thermometers were invented, improved, sold, and consumed in two distinct cultures in Britain and Japan. It argues that clinical thermometry was used for consumers' own sakes, for example, performing a gender role and dreading influenza, and also framed by such external factors as war and pandemics.